2009
DOI: 10.1089/gtmb.2009.0009
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Five ImportantCYP2D6Alleles Within an Iranian Population (Eastern Azerbaijan)

Abstract: Polymorphisms in cytochrome P450 genes encoding enzymes of critical importance for drug metabolism have the highest genetic influence on interindividual variations in drug bioavailability. Human CYP2D6 enzyme is claimed to be polymorphically expressed among different ethnic groups. It has been suggested to account for a large part of the interindividual differences in drug metabolism and pharmacokinetics. In the current investigation, 100 healthy unrelated subjects living in Tabriz, Iran, were randomly selecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…The frequency of CYP2D6*4 null allele identified in our sample (9%) was comparable with those found in the Spanish (13.8%) (Menoyo et al, 2006), South Indians (9.2%) (Naveen et al, 2006), Syrians (9.80%) (Fuselli et al, 2004), Central Italians (Fuselli et al, 2004), and the Azeri ethnic group among Iranian population (12.5%) (Kouhi et al, 2009), but was lower than those reported for Caucasians (20.7%) (Sachse et al, 1997) and Southern Spaniards (17.65%) (Fuselli et al, 2004). The other nonfunctional alleles such as CYP2D6*5 has been found at frequencies between 2% and 4% in Caucasians (Sachse et al, 1997), which resembles the previous finding in the Azeri ethnic group among the Iranian population (3.33%) (Kouhi et al, 2009). The frequency of CYP2D6-deficient alleles in different populations is shown in Table 2.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The frequency of CYP2D6*4 null allele identified in our sample (9%) was comparable with those found in the Spanish (13.8%) (Menoyo et al, 2006), South Indians (9.2%) (Naveen et al, 2006), Syrians (9.80%) (Fuselli et al, 2004), Central Italians (Fuselli et al, 2004), and the Azeri ethnic group among Iranian population (12.5%) (Kouhi et al, 2009), but was lower than those reported for Caucasians (20.7%) (Sachse et al, 1997) and Southern Spaniards (17.65%) (Fuselli et al, 2004). The other nonfunctional alleles such as CYP2D6*5 has been found at frequencies between 2% and 4% in Caucasians (Sachse et al, 1997), which resembles the previous finding in the Azeri ethnic group among the Iranian population (3.33%) (Kouhi et al, 2009). The frequency of CYP2D6-deficient alleles in different populations is shown in Table 2.…”
Section: Discussionsupporting
confidence: 86%
“…In Oriental populations, the frequency of the CYP2D6*4 allele is only around 1% or less ( Johansson et al, 1991( Johansson et al, , 1994Wang et al, 1993;Dahl et al, 1995;Jaanson et al, 2002), whereas it occurs with around 6%-7% frequency in Africans and African-Americans (Leathart et al, 1998;Griese et al, 1999). The frequency of CYP2D6*4 null allele identified in our sample (9%) was comparable with those found in the Spanish (13.8%) (Menoyo et al, 2006), South Indians (9.2%) (Naveen et al, 2006), Syrians (9.80%) (Fuselli et al, 2004), Central Italians (Fuselli et al, 2004), and the Azeri ethnic group among Iranian population (12.5%) (Kouhi et al, 2009), but was lower than those reported for Caucasians (20.7%) (Sachse et al, 1997) and Southern Spaniards (17.65%) (Fuselli et al, 2004). The other nonfunctional alleles such as CYP2D6*5 has been found at frequencies between 2% and 4% in Caucasians (Sachse et al, 1997), which resembles the previous finding in the Azeri ethnic group among the Iranian population (3.33%) (Kouhi et al, 2009).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations